Fixation of subtrochanteric extending/derotational femoral osteotomies with the Locking Compression Plate in ambulatory neuro-orthopaedic patients - Haefeli, Mathias (Springer Berlin Heidelberg, 2010)
PURPOSE: Patients with neuro-orthopaedic disorders often develop hip flexion contractures or rotational hip deformities. Increasing deformities impair the already diminished walking abilities and proximal femoral osteotomies are often performed to maintain/improve walking abilities. Fixation of the osteotomies with condylar plates has been successfully used but does often not allow immediate postoperative full weight bearing. To avoid a substantial postoperative rehabilitation deficit and additional bone loss due to inactivity, a postoperative treatment with full weight bearing is, therefore, wishful. Newer fixed-angled implants with stronger anchoring in osteopenic bone might fit these demands. The objective of this study was to evaluate bone healing and the complication rate after proximal extending and/or derotational femoral osteotomy fixed with 3.5/4.5 Locking Compression Plate (LCP; Synthes(®)) and postoperative full weight bearing in ambulatory neuro-orthopaedic patients. METHODS: Fifteen ambulatory neuro-orthopaedic patients (12 cerebral palsy [CP], 1 trisomy 21, 2 hemiparesis) with a mean age of 13.7 years (range 7–22) with hip flexion contractures and/or rotational deformities underwent subtrochanteric (n = 26) osteotomy between July 2004 and October 2007. All patients were allowed to bear their full weight postoperatively. We investigated the fusion rate, implant failure, and general complication rate until union had occurred. RESULTS: Fourteen patients (mean weight 42.0 kg [range 21.8–59]) uneventfully achieved solid fusion. One patient (19 years of age, 73 kg) needed revision surgery due to implant failure with consecutive varus deformity and achieved solid fusion after the second intervention. Besides one superficial wound infection, no other complications occurred. CONCLUSIONS: Subtrochanteric extending and/or derotational osteotomies fixed with an LCP are a reliable procedure in neuro-orthopaedic patients. Most patients can be treated with early postoperative full weight bearing. However, in heavier patients, possible implant failure must be considered.